Circulatory pattern of cytokines, adipokines and bone markers in postmenopausal women with low BMD - Azizieh FY (Dove Medical Press, 2019)
Fawaz Y Azizieh,1 Diaa Shehab,2 Khaled Al Jarallah,2 Olusegun Mojiminiyi,3 Renu Gupta,4 Raj Raghupathy51Department of Mathematics and Natural Sciences, International Centre for Applied Mathematics and Computational Bioengineering, Gulf University for Science and Technology, Kuwait City, Kuwait; 2Department of Medicine, Faculty of Medicine, Kuwait University, Kuwait City, Kuwait; 3Department of Pathology, Faculty of Medicine, Kuwait University, Kuwait City, Kuwait; 4Department of Radiology, Faculty of Medicine, Kuwait University, Kuwait City, Kuwait; 5Department of Microbiology, Faculty of Medicine, Kuwait University, Kuwait City, KuwaitObjective: In addition to some well-characterized bone turnover markers (BTMs), cytokines and adipokines have also been suggested to be linked to osteoporosis seen in menopause. However, there is much controversy on the possible association between these markers and bone mineral density (BMD). This study was aimed at measuring circulatory levels of selected cytokines, adipokines and BTMs in postmenopausal women with normal and low BMD.Methods: The study population included 71 post-menopausal women, of whom 25 had normal BMD, 31 had osteopenia and 13 had osteoporosis. Circulatory levels of selected pro-resorptive (TNF-α, IL-1β, IL-6, IL-8, IL-12, IL-17), anti-resorptive (IFN-γ, IL-4, IL-10, IL-13, TGF-β) and five adipokine markers (adiponectin, adipsin, lipocalin-2/NGAL, PAI-1 and resistin) were measured using the Multiplex system and read on the Magpix ELISA platform. Further, two bone turnover markers (PINP, CTX) as well as estradiol levels were assayed from the same samples.Results: While circulatory levels of cytokines were comparable between groups, women with low BMD had statistically significantly higher median circulatory levels of adipokines as compared to those with normal BMD. Further, while levels of CTX were not different between the two groups; PINP, PINP/CTX ratio and estradiol levels were significantly lower in women with low BMD. Levels of adiponectin, PINP, PINP/CTX ratio and estradiol correlated significantly with BMD of the hip and spine.Conclusion: The associations between various markers and BMD are complex and multivariate. Our data provide insights into the possible use of circulatory levels of cytokines, adipokines and bone turnover markers on the pathogenesis of postmenopausal osteoporosis because of the well-documented effects of these molecules on bone tissue and their relevance to osteoporosis.Keywords: cytokines, adipokines, BTM, osteoporosis, menopause